Promoting inclusion in education abroad : a handbook of research and practice - Hamir, Heather Barclay; Gozik, Nick (Stylus Publishing, 2017)
"This volume offers a combination of research-based chapters and case studies from leading experts on the barriers that disproportionately impact specific groups of students, including: students with disabilities; first-generation college students; undocumented students; racial and ethnic minorities; science, technology, engineering, and mathematics (STEM) majors; and males. The authors illuminate the issues which may inhibit education abroad participation, from individual to institutional, and present strategies reflecting a broad range of institutional contexts, resources, and needs. While there has been significant discussion and action to promote broader inclusion in education abroad, this is the first volume focusing on research and practice to achieve these ends, and is intended as a critical resource for practitioners and scholars alike"--